2023
DOI: 10.1007/s10654-022-00946-6
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of cancer diagnosis during COVID-19 pandemic: a systematic review and meta-analysis

Abstract: Many health services, including cancer care, have been affected by the COVID-19 epidemic. This study aimed at providing a systematic review of the impact of the epidemic on cancer diagnostic tests and diagnosis worldwide. In our systematic review and meta-analysis, databases such as Pubmed, Proquest and Scopus were searched comprehensively for articles published between January 1st, 2020 and December 12th, 2021. Observational studies and articles that reported data from single clinics and population registries… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…The reduction of oncologic visits found in our analysis is likely to be associated with a longer time interval from symptom onset to referral and to diagnosis, a phenomenon reported elsewhere (Abdellatif et al 2021), that combined with the decrease in cancer screening programs (Teglia et al 2022a), in visits by general practitioners and in diagnostic procedures (Angelini et al 2023), is expected to lead, according to the UK Health and Social Care Commettee (2022), to underdiagnosis and undertreatment of cancer and additional cancer deaths (Fonseca et al 2021). Hospital admissions of oncologic patients showed a global significant decrease, reaching a nadir in May 2020.…”
Section: Characteristicmentioning
confidence: 51%
See 2 more Smart Citations
“…The reduction of oncologic visits found in our analysis is likely to be associated with a longer time interval from symptom onset to referral and to diagnosis, a phenomenon reported elsewhere (Abdellatif et al 2021), that combined with the decrease in cancer screening programs (Teglia et al 2022a), in visits by general practitioners and in diagnostic procedures (Angelini et al 2023), is expected to lead, according to the UK Health and Social Care Commettee (2022), to underdiagnosis and undertreatment of cancer and additional cancer deaths (Fonseca et al 2021). Hospital admissions of oncologic patients showed a global significant decrease, reaching a nadir in May 2020.…”
Section: Characteristicmentioning
confidence: 51%
“…The multivariate linear regression analysis confirmed these results, which are coherent to the ones of a previous meta-analysis on cancer treatment during the COVID-19 pandemic (Teglia et al 2022b), in which studies from Asia showed the greatest decrease for medical, surgical, and overall cancer treatments, while those from Europe had a smaller decrease for the same outcomes and a faster recovery to pre-pandemic levels. The similarity of the results of the two analyses could be explained by the decrease in (Teglia et al 2022a, Angelini et al 2023, which probably reduced to a similar extent the number of oncologic patients to be both treated and admitted to medical facilities. Additional factors may also have played a role, for example, the decrease in the volume of patients with cancer admitted to the emergency department or transferred from outside hospitals (Zubiri et al 2021) and the decrease in available places due to the use of single-bed rooms in order to reduce nosocomial infections (Gregersen et al 2021).…”
Section: Characteristicmentioning
confidence: 88%
See 1 more Smart Citation
“…Similar estimates were found for each four-week delay in adjuvant and neoadjuvant systemic treatment and the risk of death (Hanna et al 2020 ). Previous studies showed a drop in screening rates (Chen et al 2021 ; Dinmohamed et al 2020 ; Teglia et al 2022 ), cancer reporting by pathology departments (Johansson et al 2022 ; Peacock et al 2021 ; Ribes et al 2022 ; Stang et al 2020 ) as well as the number of patients with newly identified cancer (Angelini et al 2023 ; Coma et al 2021 ; Epidemiologisches Krebsregister Baden-Württemberg 2022 ; Kaufman et al 2021 ; Morris et al 2021 ; Voigtländer et al 2021 ), and a delay of non-urgent/elective surgery (Bakouny et al 2020 ) during the COVID-19 pandemic. Significant reductions observed for all major tumor sites including breast, prostate, colorectum, and lung (Chen et al 2021 ; Coma et al 2021 ; Johansson et al 2022 ; Kaufman et al 2021 ; Morris et al 2021 ; Peacock et al 2021 ; Ribes et al 2022 ) were larger in the first COVID-19 wave around April and May 2020 compared to the second COVID-19 wave around November 2020, December 2020, and January 2021 (Coma et al 2021 ; Johansson et al 2022 ; Kaufman et al 2021 ; Peacock et al 2021 ; Ribes et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 causes disease in humans and many vertebrates [1], which facilitates the study of the pathogenic effect of SARS-CoV-2 and the testing of drugs intended for humans. In addition to typical fever and respiratory symptoms, many patients with COVID-19 experience a variety of neurological complications and cancer [2][3][4][5]. SARS-CoV-2 is distributed in many strains: B.…”
Section: Introductionmentioning
confidence: 99%